The link of socioeconomic importance to the conservation status of the Mediterranean endemic plants in Egypt - KAMAL SHALTOUT; HEBA BEDAIR; MOHAMED MAHMOUD EL-KHALAFY; AMR KESHTA; MARWA W. A. HALMY (Nusantara Bioscience, 2023)
Abstract. Shaltout K, Bedair H, El-Khalafy MM, Keshta A, Halmy MWA. 2023. The link of socioeconomic importance to the conservation status of the Mediterranean endemic plants in Egypt. Nusantara Bioscience 15: 189-211. Mediterranean Basin is the second world's richest hotspot and one of the most critical spots on the planet for endemic species. Therefore, the present study aimed at screening the Mediterranean endemics and evaluating the uses of recorded taxa quantitively through developing new indices and updating the existing ones. Indeed, Semi-structured interviews were used with 43 informants. Relative Cultural Importance (RCI), Species Conservation Importance (SCI), and Relative Medicinal Importance (RMI) indices were applied to determine the most valuable taxa. A preliminary list of 65 Mediterranean endemic species belonging to 49 genera and 22 families in Egypt was compiled from the available literature. Fifty-seven (87.7%) species have at least one aspect of the potential or actual economic value. The most represented use category was the medicinal value (39 taxa: 69.6%). Thymbra capitata (L.) Cav. was mentioned in the highest use categories (NU: 5). Veronica syriaca Roem. & Schult. attained the maximum ethnobotanical Relative Importance (RI) index value. It is crucial to shed light on the cultural value of Mediterranean endemics to guide future management planning to support the conservation and sustainable use of these critical species.